2016
DOI: 10.1371/journal.pone.0150753
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of A1c Predicts Diabetes Self-Management and A1c Level among Chinese Patients with Type 2 Diabetes

Abstract: This study was to identify current A1c understanding status among Chinese patients with type 2 diabetes, assess if knowledge of A1c affects their diabetes self-management and their glycemic control and recognize the factors influencing knowledge of A1c among patients with type 2 diabetes. A multi-center, cross-sectional survey was conducted between April and July 2010 in 50 medical centers in the Mainland China. Participants were recruited from inpatients and outpatients who were admitted to or visited those m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 19 publications
(29 reference statements)
4
23
0
1
Order By: Relevance
“…This means that when adults with T2DM have more diabetes knowledge, they are more likely to perform DSM in better ways for their health. This findings is consistent with findings from previous studies (Asmamaw et al., 2015; Kueh et al., 2015; van der Heide et al., 2014; Yang et al., 2016) and SCT (Bandura, 2004). To enhance the likelihood of DSM being practised among adults with T2DM in Vietnam, healthcare professionals need to advise their clients of the importance of monitoring their blood glucose levels and the meaning of A1C (Yang et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This means that when adults with T2DM have more diabetes knowledge, they are more likely to perform DSM in better ways for their health. This findings is consistent with findings from previous studies (Asmamaw et al., 2015; Kueh et al., 2015; van der Heide et al., 2014; Yang et al., 2016) and SCT (Bandura, 2004). To enhance the likelihood of DSM being practised among adults with T2DM in Vietnam, healthcare professionals need to advise their clients of the importance of monitoring their blood glucose levels and the meaning of A1C (Yang et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This findings is consistent with findings from previous studies (Asmamaw et al., 2015; Kueh et al., 2015; van der Heide et al., 2014; Yang et al., 2016) and SCT (Bandura, 2004). To enhance the likelihood of DSM being practised among adults with T2DM in Vietnam, healthcare professionals need to advise their clients of the importance of monitoring their blood glucose levels and the meaning of A1C (Yang et al., 2016). Healthcare professionals in Vietnam also need to provide advice on appropriate DSM activities (Kueh et al., 2015) and individualize their advice for diabetes management (van der Heide et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with uneducated individuals, higher educational attainment was statistically associated with a better understanding of HbA1c measurements . It has been reported that only a minority of patients with T2DM in China understand the implications of their HbA1cmeasurements . Better diabetes self‐management behavior and good glycemic control will be formed in patients who are aware of the significance of HbA1c levels.…”
Section: Discussionmentioning
confidence: 99%
“…HbA 1c measurement is an essential indicator for optimal quality of diabetes care. Studies have found an association between adherence to HbA 1c measurement and quality outputs [26][27][28].…”
Section: Discussionmentioning
confidence: 99%